Enemy at the gates: Safety and Security in Philippine Schools - Samala , Hazel DR.; Ogale , Geoffrey S.; Ogale , Marishyrl M. (International Journal of Psychosocial Rehabilitation, 2020)
This literature review presents the existing policies and guidelines on safety and security of the Department of Education (DepEd), Commission on Higher Education (CHED), as well as legislative orders pertaining to safety and security among Philippine schools. For decades, there are existing documents that aim to guide educational sector on how practice safety procedures but despite the presence of these guidelines, the country is still left behind in terms of the following: (1) specific guidelines on hiring security personnel and their qualifications; (2) process on maintaining these security personnel; and (3) modern facilities and equipment that will help the security personnel perform their tasks in securing the safety of both students and teachers. With numerous incidents happened in the school community in the past years, some resulted to death of Filipino students and teachers while in school premises, it’s time that the Philippine government should focus on improving the guidelines in safety and security in the academe.